P11. Differential diagnosis of acute psychosyndrome and seizure. Issue 8 (August 2018) - Nikolic, M.; Schreiber, S.; Uhl, J.; Heinsius, V.; Wallenfelsová, E.
Abstract : We report the case of a 43-year-old female patient with a history of intermittent visceral abdominal pain, who presented with an acute psychosyndrome with psychomotor agitation. In addition, the patient suffered a generalized epileptic seizure immediately upon arrival to the intensive care unit. She received clonazepam and levetiracetam i.v. The cerebral MRI showed bilateral occipital edematous changes, which we interpreted as PRES in the initial context of a hyponatremia of 120 mmol/l. As serum sodium levels continued to fall while urine sodium levels were continuously high, substitution was started under intensive-care monitoring and Fludrocortison co-administration. A spinal tap analysis did not show any acute inflamation. The antineural antibodies, specific for autoimmune encephalitis were also negativ. Consideration of the unexplained abdominal pains, a history of dark coloured urine and the acute neurological symptoms described above led us to the suspected diagnosis of an acute intermittent porphyria. Accordingly to the working diagnosis the patient was treated with a high dose of glucose. An acute hepatic porphyria was confirmed through the detection of the corresponding metabolic parameters ( δ -ALS, PBG, porphyrins in the urine and porphyrins in the stool). The entire clinical picture was interpreted as PRES in an exacerbated acut hepatic porphyria with the following syndrome of inadequate ADH secretion. Under treatment, the patient stabilised clinically, no PRES-typical changes remained in the follow-up MRI. The anticonvulsive medication was terminated and the patient was discharged in a stable general condition into ambulatory special care.